Alocação ótima simultânea de geradores fotovoltaicos e de sistemas de armazenamento de energia em sistemas de distribuição de energia elétrica - SANTOS, Igor Soares dos (2018)
In this work, the problem of the allocation of photovoltaic generators and energy storage systems simultaneously in an electric power distribution system is formulated and solved, observing the minimization of active losses in the network, while operational network restrictions are satisfied. To properly consider the imbalance characteristic of distribution networks, a three-phase approach to the feeder and its components is considered using OpenDSS software. The solution of the problem is done using the stochastic search algorithm Evolution Strategy to optimize the proposed objective function. For this purpose, the Evolution Strategy technique with adaptation of covariance matrix of the population was implemented, which aims to improve the probability that good individuals will happen again throughout the evolutionary process. To illustrate the methodology, the IEEE-13 test distribution system was used in three different test cases. The results obtained adequately illustrate the proposed formulation and its practical utility. The solution solved through the evolutionary algorithm presents good results in the reduction of technical losses of the system, while simultaneously allocating photovoltaic generators and storage systems in the electric distribution system.